'Own your narrative': teenagers as producers and consumers of porn in Netflix's Sex Education. Issue 4 (12th March 2022) - Dudek, Debra; Woodley, Giselle; Green, Lelia
ABSTRACT: Netflix's Sex Education both represents sex education and educates viewers about sex. From the opening scene of the first episode, viewers are positioned to see this series as one that is not afraid to represent explicitly the details of a range of sexual experiences. The series' frank depiction of sexual relationships between characters, and its exploration of characters' hopes, fears, and choices regarding ways to express their sexual desire is, arguably, ground-breaking. This paper focuses upon the ways in which the series represents young people as producers and consumers of pornographic/erotic narratives, harnessing the communication options within their social settings to develop understandings of, and share, information that is often structured as 'inappropriate' for under-18 year-olds. Sex Education sits at the intersection of information (seeking), communication, and society, as young people explore issues of crucial interest and importance to them, which have been all but ignored in most of their school curriculum offerings. Challenging a dominant social perception of sexually-explicit materials as harmful to young people, and suggesting instead that such materials may be beneficial, the series demonstrates how young people may come together to learn about themselves and each other, even as they confront the double standards of a hypersexualised society that offers no legitimate speaking position to under-18s. In this environment, with adults absent from authentic discussion, young people co-construct their future adult selves through producing, consuming, and discussing sexual content (and activities) in conversation with other young people.